2019
DOI: 10.1002/jor.24534
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory, Structural, and Pain Biochemical Biomarkers May Reflect Radiographic Disc Space Narrowing: The Johnston County Osteoarthritis Project

Abstract: The purpose of this work is to determine the relationship between biomarkers of inflammation, structure, and pain with radiographic disc space narrowing (DSN) in community-based participants. A total of 74 participants (37 cases and 37 controls) enrolled in the Johnston County Osteoarthritis Project during 2006-2010 were selected. The cases had at least mild radiographic DSN and low back pain (LBP). The controls had neither radiographic evidence of DSN nor LBP. The measured analytes from human serum included N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…With cluster representing lower levels of biomarkers as the referent, a significant association was found among cases with disc space narrowing compared to controls without disc narrowing for the cluster with higher levels of OPG, Regulated on Activation, Normal T Cell Expressed and Secreted (RANTES), keratin-19 and lumican and neuropeptide-Y. A significant association was also found with cases with disc space narrowing compared to controls without disc space narrowing in the cluster represented with a higher levels of neuropeptide Y (40).…”
Section: Efficacy Of Interventionmentioning
confidence: 82%
“…With cluster representing lower levels of biomarkers as the referent, a significant association was found among cases with disc space narrowing compared to controls without disc narrowing for the cluster with higher levels of OPG, Regulated on Activation, Normal T Cell Expressed and Secreted (RANTES), keratin-19 and lumican and neuropeptide-Y. A significant association was also found with cases with disc space narrowing compared to controls without disc space narrowing in the cluster represented with a higher levels of neuropeptide Y (40).…”
Section: Efficacy Of Interventionmentioning
confidence: 82%
“…In fact, low serum levels of OPG are commonly observed in patients with multiple myeloma suffering from severe bone pain (Vellucci et al, 2018). In addition, a significant association was recently reported between the serum levels of OPG and the severity of radiographic space narrowing in subjects with low back pain (Goode et al, 2020). Thus, the upregulation of OPG synthesis might be deeply associated with the amelioration of low back pain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to biochemical changes within IVDs, prior studies have identified relationships between serum biomarkers (including NPY and RANTES) and musculoskeletal disorders, including back pain 41,57–60 . NPY and RANTES are both expressed by the IVD and are associated with symptomatic LBP in humans 41,61–64 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to biochemical changes within IVDs, prior studies have identified relationships between serum biomarkers (including NPY and RANTES) and musculoskeletal disorders, including back pain. 41 , 57 , 58 , 59 , 60 NPY and RANTES are both expressed by the IVD and are associated with symptomatic LBP in humans. 41 , 61 , 62 , 63 , 64 Our results showed consistently higher serum concentrations of NPY in the experimental group compared to the control or sham groups beginning 6 weeks after the annular puncture, consistent with prior research associating higher levels of serum NPY with symptomatic back pain.…”
Section: Discussionmentioning
confidence: 99%